2018
DOI: 10.1186/s40249-018-0478-4
|View full text |Cite
|
Sign up to set email alerts
|

Containment measures for emerging and re-emerging vector-borne and other infectious diseases of poverty in urban settings: a scoping review

Abstract: BackgroundThe emergence and re-emergence of vector-borne and other infectious diseases of poverty pose a threat to the health of populations living in urban and low-income settings. A detailed understanding of intervention strategies, including effectiveness of past outbreak containment, is necessary to improve future practices. The objective was to determine what is known about the effectiveness of containment measures for emerging and re-emerging vector-borne and other infectious diseases of poverty in urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Although the state of knowledge on this virus is still limited and constantly evolving, evidence of the effectiveness or the processes to be used to develop or organise speci c actions is already available. For example, regarding containment measures, a scoping review synthesising relevant knowledge published in 2018 highlights the importance of community involvement for their effectiveness [36]. A study on Ebola in 2014-2016 in the region similarly showed the need for community involvement in disease control interventions that take into account local dynamics [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although the state of knowledge on this virus is still limited and constantly evolving, evidence of the effectiveness or the processes to be used to develop or organise speci c actions is already available. For example, regarding containment measures, a scoping review synthesising relevant knowledge published in 2018 highlights the importance of community involvement for their effectiveness [36]. A study on Ebola in 2014-2016 in the region similarly showed the need for community involvement in disease control interventions that take into account local dynamics [34].…”
Section: Discussionmentioning
confidence: 99%
“…It also contributes to decreasing the potential for biases and ensures the generation of robust evidence. Therefore, given the strength of the McGill University team on quantitative social epidemiologic methods, we shared a theoretical background (15) and some empirical results (12,16) throughout the activities. As methodological tools to mitigate such challenges, we proposed the use of quasi-experimental designs, propensity score techniques, and models accounting for measurement error in the analysis of health inequalities on arboviruses.…”
Section: Social Determinants and Social Epidemiology Methodsmentioning
confidence: 99%
“…The activities initiated without any specific source of funding and, therefore, the members developed a work plan to be submitted for funding to different Canadian and Cuban agencies. Given the expertise of the collaborating institutions and previously identified knowledge gaps in our research and the literature on arboviral research (9,10,1214), we selected three main work thematic areas: social determinants of health and equity, community-based interventions, and knowledge transfer. The objectives of the collaboration were (a) to provide scenarios to highlight the contributions of social sciences into research in global health, and (b) to promote the scientific exchange and knowledge dissemination between researchers from Quebec, Cuba, and the international academic community.…”
Section: Institutional Scientific Collaborationmentioning
confidence: 99%
See 2 more Smart Citations